Rapid Reverse-phase High-performance Liquid Chromatography Estimation of Methotrexate in Bulk, Pharmaceutical Preparation and in Spiked Plasma Samples: Rapid Reverse-phase High-performance Liquid Chromatography Estimation of Methotrexate in Bulk, Pharmaceutical Preparation and in Spiked Plasma Samples - Agrawal, Ashish (International Journal of Pharmaceutical & Biological Archive, 2019)
A simple, sensitive, and selective reverse-phase high-performance liquid chromatography (RP-HPLC) method with ultraviolet (UV) detection for the estimation of methotrexate in pharmaceutical formulation and in spiked plasma developed and validated in the present work. Chromatographic separation of drug is performed with a 250 mm Ã— 4.6 mm, 5 Î¼m diameter particles RP C-18 column and the mobile phase consisted of a mixture of methanol and water (80:20, v/v), containing 0.1% HPLC-grade glacial acetic acid for the adjustment of pH to 4.5. Isocratic elution at a flow rate of 1 ml/min with UV detection at 256 nm at ambient temperature is used in this method. The proposed RP-HPLC method is successfully applied for the determination of methotrexate in pharmaceutical preparation and spiked plasma samples. The validation studies are carried out and itâ€™s fulfilling ICH requirements. The method is found to be specific, linear, precise (including both intra- and inter-day precision), accurate, and robust. This proposed method may represent a valuable aid in the laboratory monitoring of the toxicity of anticancer chemotherapy.